Associations between parent–child relationship quality and obesogenic risk in adolescence: a systematic review of recent literature. (29th April 2016) - Blewitt, Claire; Bergmeier, Heidi; Macdonald, Jacqui A.; Olsson, Craig A.; Skouteris, Helen
Summary: Adolescence is a period of significant cognitive, social and physiological change, presenting unique risk factors for weight gain. Childhood obesity research has traditionally focused on the influence of parent‐level factors on children's eating and weight status. Increasingly, emphasis is turning towards the reciprocal nature of the parent–child relationship and its influence on health behaviour. A systematic literature review was conducted to investigate the relationship between parent–child relationship quality (defined as the felt emotional bond between parent and child) and obesogenic risk (weight status, eating attitudes and behaviours, level of physical activity and sedentary behaviour) in adolescence; 26 papers were included in the review. The results neither support nor challenge an association between parent–child relationship quality and weight, with study design flaws and limited measurement of the parent–child relationship precluding robust conclusions. The review does however suggests that several aspects of the parent–child relationship are important in understanding eating attitudes and behaviours, including the felt emotional bond between the parent and child, the child's perception of how much the parent cares for them and the mother's sensitivity towards the child. The need for further longitudinal research into the association between parent–child relationship quality and obesity risk across this developmental period is discussed.